Autologous stem cell transplantation : biological and clinical results in malignancies - Carella, Angelo Michele (Harwood Academic Publishers, 1997)
Autologous Stem Cell Transplantation integrates basic research and clinical aspects underlying the most recent results in those malignant diseases where progress is most effective.Recent evidence shows that higher doses are better in inducing higher cure rates in hematological neoplasias, although myeloblation related to dose intensity can be a limiting factor. The toxicity can now be controlled with autologous marrow and peripheral blood progenitor cell transplantation, used with or without growth factors. The combination of high dose chemoradiotherapy followed by re-infusion of autologous stem cells constitute a dramatic advance in the treatment of refactory and relapse hematological neoplasias.
Advances in blood disorders ; vol. 2
Keywords: transplantace kostní dřeně; Transplantace kmenových buněk; kmenové buňky; Stem Cells; Bone Marrow Transplantation; Buňky kmenové